Solvability and Trajectory-Final Controllability of Pseudohyperbolic Systems - Nomirovs'kii, D. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We consider the problem of solvability and optimization for a pseudohyperbolic operator of the general form. We prove theorems on existence and uniqueness for various right-hand sides of the equation. The results obtained are applied to the problem of trajectory-final controllability.